The Evaluation of Enterprise Information Systems and Electronic Records Management Standards within the scope of TS 13298: A Case of the Ministry of Internal Affairs - Eroğlu, Şahika; Külcü, Özgür (Information World, 2014)
As in many areas IT Technologies has led to various changes for the implementation of public services and relationships between the citizen and governments In this context, enterprise information systems used in enterprise services is mainly based on electronic document management applications. Document management, enterprise information systems, electronic document management and standards are analyzed under the national legislations in this study. In this respect, main aim of the study is to determining system requirements for electronic document management program in institutions and their suitability for TS13298 standard via an assessment tool developed in accordance to TS13298 Electronic Document Management Standard. From this point the assessment tool developed within the standart of TS13298 and consists of 40 items, applied at the Ministry of Interior Affairs that was carried out an intensity application example of the implementation of electronic document management. In the end of the study, required improvements of the electronic document management systems implemented in the organization and its compliance level are reported.
Keywords: Enterprise information systems; electronic document management; TS 13298; e-İçişleri